2017
DOI: 10.2298/sarh160712062r
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax as a complication of cardiac rhythm management devices implantation

Abstract: Introduction/Objective Pneumothorax is one of the most common complications of cardiac rhythm management (CRM) devices implantation. We aimed to assess the incidence of pneumothorax after implantation of these devices and to determine risk factors for this complication. Methods A retrospective, observational study included patients in whom CRM devices were implanted, pacing system was upgraded, or lead revision was performed during 2012 at the Pacemaker Center, Clinical Center of Serbia. We determined the conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Finally, the same group of authors from the Pacemaker Center of the Clinical Center of Serbia reported the rate of pneumothorax, one of the most common complications of cardiac rhythm management devices, including antibradycardia pacemakers, implantable cardioverter defibrillators, and CRTs, during one year [5]. Among 999 patients, the rate of pneumothorax was 1.8% (incidence from the literature data is 0.66-5% [10]), and more often found in women, older patients, subclavian vein puncture, and the use of intravenous contrast during the procedure.…”
Section: Developments Of Interventional Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the same group of authors from the Pacemaker Center of the Clinical Center of Serbia reported the rate of pneumothorax, one of the most common complications of cardiac rhythm management devices, including antibradycardia pacemakers, implantable cardioverter defibrillators, and CRTs, during one year [5]. Among 999 patients, the rate of pneumothorax was 1.8% (incidence from the literature data is 0.66-5% [10]), and more often found in women, older patients, subclavian vein puncture, and the use of intravenous contrast during the procedure.…”
Section: Developments Of Interventional Techniquesmentioning
confidence: 99%
“…and devices for the treatment of coronary artery disease, structural heart diseases, including valvular and congenital heart disease, as well as heart failure, have changed the practice of modern cardiology. In this issue of the Serbian Archives of Medicine we present five articles on different novel techniques, devices, as well as complications of device implantation for the treatment of chronic total occlusion [1], aortic valve disease [2], patent ductus arteriosus [3], pacemaker systems upgrade [4], and finally critical analysis of the most common complications during the implantation of cardiac rhythm management devices [5].…”
Section: Developments Of Interventional Techniquesmentioning
confidence: 99%